IMPROVING STUDENTS’ ENGLISH-SPEAKING PERFORMANCE BY USING CAKE APPLICATION - Riki; Regina; Wardah (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This research aimed to describe how Cake application improves the English speaking performance of the tenth grade students at SMK Negeri 01 Mempawah Hilir. Based on the researcher’s observation, the students encountered several problems in speaking English. Most students faced problems in pronouncing words due to lack of pronunciation mastery. The students also faced difficulty to speak English fluently due to lack of confidence and afraid of making mistakes. Therefore, the researcher used Cake application to improve students’ English speaking performance. This Classroom Action Research was conducted in two cycles on the tenth grade students of Marketing Class which consisted of 31 students. The research data were collected through observation and measurement techniques by using field notes, observation checklists, and tests. In cycle I, the mean score of students’ speaking test was 75.16. Meanwhile, the percentage of classical completeness was 67% of 31 students, which did not meet the expected percentage of this research (90%). In cycle 2, the mean score of students’ speaking test increased to 83.19. The percentage of classical completeness increased to 93%, which met the expected percentage of this research (90%). The research findings show that Cake application has improved the students' English speaking performance.